Landscape with water from Maupassant and Chekhov (On the Water and Seagull) - Ищук-Фадеева, Нина (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2010)
The article is dedicated to the comparative analysis of water metaphors in Maupassant’s and Chekhov's comedies, which enables a clear understanding of the nature of their heroes. This, in turn, helps understand the nature of art and the picture of the world in general.